Thermal coupled extractive distillation sequences with three entrainers for the separation of azeotrope isopropyl alcohol + diisopropyl ether. Issue 5 (18th February 2020) - Zhang, Yi; Li, Ao; Gao, Jun; Xu, Dongmei; Zhang, Lianzheng; Zhang, Zhishan; Wang, Yinglong
Abstract: BACKGROUND: During the synthesis of isopropyl alcohol (IPA) by hydration of propylene, diisopropyl ether (DIPE) is usually produced as a by‐product. Because IPA and DIPE can form a binary homogeneous azeotrope with the minimum boiling temperature at atmospheric pressure, it is difficult to separate the binary mixture by simple distillation. RESULT: For separating the azeotrope IPA + DIPE, side‐stream extractive distillation column (SSED) and extractive dividing wall column (EDWC) processes with three entrainers [2‐methoxyethanol (2‐MEA), 2‐ethoxyethanol and propylene glycol ethyl ether (PGEE)] were simulated and optimized based on the minimal total annual cost (TAC). Moreover, CO2 emissions of the six sequences were calculated and the impact on the environment evaluated. CONCLUSIONS: The sequence of SSED with PGEE as entrainer can reduce TAC by ≤34.48%, but EDWC with PGEE can offer TAC reduction of ≤52.46%. The results demonstrate that the EDWC sequence with PGEE as entrainer is favourable for separating the binary azeotrope IPA + DIPE. © 2020 Society of Chemical Industry